Engagement y productividad de los trabajadores del Instituto Superior Sabio Nacional Antúnez de Mayolo De Iquitos, 2024 - Salazar del Castillo, Gabriel Alcides (2024)
In this research, the central objective was to determine the type of relationship that exists between engagement and productivity, in the work context, in a company in the higher education sector of the city of Iquitos. It is a descriptive correlational scope study that used a non-experimental cross-sectional design. The research technique used was the survey with two structured Likert-type questionnaires. The sample was non-probabilistic, which was made up of the company's fourteen workers. The processing of the data reveals that 93% of those surveyed say they have a very high level of engagement and productivity, and the remaining 7% have a high level. The central hypothesis test was done with Spearman's correlation coefficient, which reached a value of 0.856 with a p-value of 0.001, based on which the research hypothesis is verified, in the sense that the relationship between engagement and productivity is very intensely positive, and this is statistically significant.